Altitude, habitat type and herbivore damage interact in their effects on plant population dynamics - Dostálek, Tomáš; Rokaya, Maan Bahadur; Münzbergová, Zuzana (PloS one, 2018)
Insects represent one of the most abundant groups of herbivores, and many of them have significant impacts on the dynamics of plant populations. As insects are very sensitive to changes in climatic conditions, we hypothesize that their effects on plant population dynamics will depend on climatic conditions. Knowledge of the variation in herbivore effects on plant population dynamics is, however, still rather sparse. We studied population dynamics and herbivore damage at the individual plant level of Salvia nubicola along a wide altitudinal gradient representing a range of climatic conditions. Using integral projection models, we estimated the effect of changes in herbivore pressure on plant populations in different climates and habitat types. Since we recorded large differences in the extent of herbivore damage along the altitudinal gradient, we expected that the performance of plants from different altitudes would be affected to different degrees by herbivores. Indeed, we found that populations from low altitudes were better able to withstand increased herbivore damage, while populations from high altitudes were suppressed by herbivores. However, the pattern described above was evident only in populations from open habitats. In forest habitats, the differences in population dynamics between low and high altitudes were largely diminished. The effects of herbivores on plants from different altitudes were thus largely habitat specific. Our results indicate potential problems for plant populations from high altitudes in open habitats because of increased herbivore damage. However, forest habitats may provide refuges for the plants at these high altitudes.
Keywords: Behavior, Animal; Salvia; Animals; šalvěj; Herbivory; nadmořská výška; zvířata; Population Dynamics; ekosystém; Altitude; populační dynamika; Ecosystem; chování zvířat; býložravci